Premeščanje in spreminjanje pogodbe o zaposlitvi z vidika pogodbenosti uslužbenskih razmerij - Korpič-Horvat, Etelka (Delavci in delodajalci, 2009)
In her contribution the authoress deals with special features regarding regulation of employment relationships for the employed within the public sector as laid down in the Civil Servants Act related to relocation and alterations of the employment contract for civil servants within public authorities and the administrations of self governing local communities. She believes that the contractual nature of the employment relationship is curtailed by the possibility of unilateral changes of certain elements of the employment contract by the decision of the principal or by the institute of relocation and partial or complete invalidation of the employment contract by the Appeals Board. To protect public interest, the principal, though entitled to unilateral alternations of the employment contract is bound to strictly observe the law, other acts and collective agreements. Contrary to other member states of the European Union, in Slovenia the employees within the public sector do have an employment contract. Accordingto the authoress it should be possible to implement the principle of equalising the situation of public servants and even more so of professional technical staff employed within the public sector with those of other workers more vigorously.
Keywords: delovna razmerja; javna uprava; javni interes; javni uslužbeci; pogodba o zaposlitvi; spremembe; zaposleni